THE EFFECT OF HEALTH EDUCATION IN HOMECARE SERVICES ON THE INDEPENDENCE OF DAILY ACTIVITIES OF MIDDLE STROKE PATIENTS IN KEC. KOLANG 2021 - Devi Kristina Hutagalung; Piuskosmas Fau; Delvi Sihombing (Institute of Computer Science (IOCS), 2022)
Health education is one form of nursing intervention that can be carried out in nursing services. Home care is a form of nursing service in the community.. This study aims to determine the effect of health education in the implementation of home care on the independence of daily activities for patients with mild stroke in Kec.Kolang. The research design used in this study was a preexperimental method with one group pretest-posttest design, namely research using one group of subjects, measurements were carried out before and after giving treatment to the subject with a sample of 10 people. The daily activity independence score after health education showed an increasing trend. Respondents belonging to the independent category experienced an increase from 3 people (30%) at the pre-test to 8 people (80%) at the posttest with the strength of the influence p=0.016. Respondents belonging to the